Integrated Process Design for n-Octane Production Enhancing Yield and Energy Saving via Recycle, Heat Integration, and Purge-gas Utilization - Muhammad Bialfan Purasetya; Achika Risky Yustifasari; Agnes Advencia Sagita; Amara Wahyu Ardinta; Nanda Angelica Basaria Sinaga (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
n-octane is an essential hydrocarbon in fuels and petrochemicals, yet conventional production suffers from high energy demand and material losses. This study develops an integrated process design combining recycle systems, heat integration, and purge-gas utilization for n-octane production. Results show that recycle integration raises yield from 92.81% to 97.46%, heat integration achieves 36.38% energy savings, and purge-gas valorization sustains high yield (97.41%) while delivering the greatest energy reduction (62.30%). The findings demonstrate that synergistic process intensification enhances efficiency and sustainability, offering a transferable framework for hydrocarbon production optimization. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).